Pengaruh Edukasi Terhadap Kontrol Glikemik Pada Pasien Diabetes Mellitus Tipe 2 - Yusuf, Bahtiar; U’Adia B.Achmad, Chotimah; Yuliati, Yuliati (Nursing Arts, 2024)
Diabetes Mellitus (DM) is a metabolic disorder characterized by hyperglycemia due to abnormalities in insulin secretion, insulin action or both and is one of the largest contributors to death in the world. Prevention of DM complications is by ensuring that blood glucose levels in the body remain controlled, efforts made through four pillars of DM management, one of which is providing education. Nurses as educators can provide education to increase knowledge regarding changes in attitudes and behavior of DM sufferers thereby increasing compliance and quality of life. Objective: of this research is to determine the effect of education on glycemic control in people with type 2 diabetes mellitus in the work area of the Central Fakfak Community Health Center. Method: used in this research is a case study design with analytical descriptive research type using 2 research subjects, data collection was carried out using the DKQ questionnaire and a glucometer to measure glycemic levels. Results: This study shows that pre-test and post-test measurements using the DKQ questionnaire increased both respondents' knowledge with the blood glucose test while respondent 1 experienced a decrease of 19 mg/dl and respondent 2 experienced a decrease of 68 mg/dl. after several weeks of education given in three visits. Conclusion: in this study, education can increase knowledge of self-management and behavior as well as motivation to be healthy so that it can control the glycemic levels of someone with DM.